Standardization of organic manure application in pomegranate (Punica granatum) orchards grown in semi-arid regions - MARATHE, R A; SHARMA, JYOTSANA; SHINDE, Y R; CHAUDHARI, D T (The Indian Journal of Agricultural Sciences, 2016)
An experiment was conducted at ICAR - National Research Centre on Pomegranate during 2011-12 and 2012-13 on pomegranate (Punica granatum L) cv. Bhagwa plants. The experiment comprises of application of raw and well decomposed farmyard manure in the form of slurry (liquid form, manures mixed with water in 1:10 ratio and kept for 10 to 15 days with intermittent stirring) as a sole or in combination with micronutrients and/or various microbial inoculants. It was compared with normally practiced method of organic manure application in the soil. The results revealed that application of farmyard manure in slurry form decreased electrical conductivity (0.94 to 0.72 dS/m) and increased organic carbon content (0.55 to 1.45 %) in the soil. Combined application of FYM in the form of slurry along with micronutrients and microbial inoculants significantly increased available N (339.7 kg/ha) and P (34.8 kg/ha) and micronutrients content in the soil. Substantially increased plant height (20.8%), plant spread (22.8 %) and produced maximum number of fruits (39.0/ plant). Population of soil microbes, viz. Aspergillus niger, Pseudomonas fluorescence and potash solubilising organisms were significantly highest with the combined application of FYM in slurry form and microbial inoculants. While, Azotobacter population was more in raw FYM slurry along with microbial inoculants. It is recommended that on light textured soils, farmyard manures should be applied in the form of slurry. It reaches in the active root zone of the plants along with percolating water.